Peran Guru dalam Mengembangkan Pendidikan Karakter melalui Kurikulum Merdeka di SDN Aeng Panas 1: The Role of Teachers in Developing Character Education through the Merdeka Curriculum at SDN Aeng Panas 1 - Punggeti, Ratna Novita; Prijambodo, Raden Firman Nurbudi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Through a case study of SDN Aeng Panas 1, this research delves into the role of teachers in implementing the Merdeka Curriculum for student character development. A case study research design was chosen because it allows the researcher to conduct an in-depth analysis of a specific context, namely SDN Aeng Panas 1. This case study will provide a comprehensive overview of how character education is implemented through the Merdeka Curriculum, including the strategies used, the challenges faced, and the outcomes achieved. The findings indicate that teachers have successfully integrated character education into various subjects using active and participatory learning methods. Despite challenges such as limited resources and inconsistent support, teachers have demonstrated a high level of commitment. This study recommends enhancing teacher competencies, providing adequate resources, and fostering closer collaboration with parents and the community to strengthen character education programs.